Design of high torque density motors for quadruped robot hip joints - YANG Heming; LIANG Bo; DOU Manfeng; DANG Mengxi; HUA Zhiguang (Xibei Gongye Daxue Xuebao)
In response to the high torque density performance requirements for the hip joints of quadruped robots, an analytical design method for permanent magnet synchronous motors with the goal of increasing motor torque density is proposed in this study. A high torque density motor for quadruped robot hip joints is designed using this method. Finite element simulation is employed to model the motor, and a proof-of-concept prototype is designed based on the proposed analytical design method. Simulation and experimental data indicate that the designed motor's torque density meets the practical application requirements for quadruped robot hip joints, validating the accuracy and effectiveness of the analytical design method presented in this study.